Carnegie-Rochester conference series on public policy - University of Rochester. Center for Research in Government Policy and Business; Carnegie Mellon University. Graduate School of Industrial Administration; William E. Simon Graduate School of Business Administration (North-Holland, 2001)
Each vol. consists of papers and discussions from the semi-annual Carnegie-Rochester Conference on Public Policy.
Keywords: Economic policy : Congresses; Economic policy : Congresses : Periodicals; Politique économique : Congrès : Périodiques; Politique économique : Congrès; Bibliographies; Congrès; Politique économique; Publications périodiques; Economic policy; Overheidsbeleid; Collectieve sector